2019
DOI: 10.1101/764910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of genome architecture and chromatin function during human B cell differentiation and neoplastic transformation

Abstract: Despite recent advances, the dynamics of genome architecture and chromatin function during human cell differentiation and its potential reorganization upon neoplastic transformation remains poorly characterized. Here, we integrate in situ Hi-C and nine additional omic layers to define and biologically characterize the dynamic changes in three-dimensional (3D) genome architecture across normal B cell differentiation and in neoplastic cells from different subtypes of chronic lymphocytic leukemia (CLL) and mantle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 115 publications
(140 reference statements)
1
4
0
Order By: Relevance
“…Application of our method to a model system of human B cell differentiation has revealed how a core network of transcription factors exercise regulatory control over B cell differentiation, explicitly coupled to the CD40 and BCR activation stimuli administered to the in vitro cell system. In many cases, observed regulation downstream of CD40 and BCR signals is consistent with regulatory dynamics observed in ex vivo murine B cells stimulated by lipopolysaccharide (LPS) (5,39,40) as well as in primary human B cell populations (8,10). Findings reported in these studies, in conjunction with the analyses presented here, suggests that common mechanisms define genetic regulation during B cell activation and plasma cell differentiation; characterised by declining regulation at PU.1/SPIB associated motifs and increased regulation at motifs occupied by NF-κB, AP-1, IRF4, OCT2, E2A (E-Box) and MEF2 factors (MADs-Box).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Application of our method to a model system of human B cell differentiation has revealed how a core network of transcription factors exercise regulatory control over B cell differentiation, explicitly coupled to the CD40 and BCR activation stimuli administered to the in vitro cell system. In many cases, observed regulation downstream of CD40 and BCR signals is consistent with regulatory dynamics observed in ex vivo murine B cells stimulated by lipopolysaccharide (LPS) (5,39,40) as well as in primary human B cell populations (8,10). Findings reported in these studies, in conjunction with the analyses presented here, suggests that common mechanisms define genetic regulation during B cell activation and plasma cell differentiation; characterised by declining regulation at PU.1/SPIB associated motifs and increased regulation at motifs occupied by NF-κB, AP-1, IRF4, OCT2, E2A (E-Box) and MEF2 factors (MADs-Box).…”
Section: Discussionsupporting
confidence: 63%
“…B cell differentiation is driven through changes in genetic regulation, where regulatory circuits are rewired through dynamic shifts in epigenetic remodelling and transcription factor activity. Genome wide studies of epigenomic, transcriptomic and conformational datasets have been instrumental in uncovering how the chromatin environment shapes B cell populations, and responds to stimuli to determine cell fate (5,8,10,35,39,40). However, there are gaps in our understanding of the complex associations between cis and trans acting factors which fine-tune transcription to orchestrate B cell maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to evaluate variances in HOXA5 expression in different grades of endometrial cancer. In addition, it should be remembered that the process of neoplastic transformation is extremely dynamic and varies to some extent in different types of cancer [ 23 ]. The study of Ordóñez-Morán et al using IHC staining in colorectal cancer showed a low level of HOXA5 in stem cells and high expression in differentiated villi, suggesting that HOXA5 is strongly associated with regulation of metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Compartments become intensely rearranged during cellular differentiation and reprogramming [24–29]. For instance, as demonstrated by Hi‐C, along the in vitro differentiation path from human embryonic stem cell (ESC) to cardiomyocyte, nearly one‐fifth of the genome switches from the one compartment to the other [24].…”
Section: Intranuclear Consensus By Dna–fish and 3c Approachesmentioning
confidence: 99%